The influence of localized mechanical stresses on the non-homogeneous distribution of electrical conductivity. Issue 6 (7th November 2016) - Napieralska-Juszczak, Ewa; Napieralski, Piotr; Komeza, Krzysztof; Zeroukhi, Youcef
Abstract : Purpose: The purpose of this paper is to determine the physical design parameters that influence the total resistance of a twisted conductor (cable). One of the physical parameters characterizing this type of structures is the uneven distribution of resistivity due to hardening, which is the result of stress exerted on the wires during the manufacturing process. Design/methodology/approach: The authors have developed a method to take into account the effect of localized hardening on the inhomogeneous distribution of electrical conductivity in the distorted structures of the conductor. To achieve this goal, the authors have implemented a mechanical-electrical simulation method. The resistance characteristics have been measured as a function of mechanical stress. Findings: As demonstrated by the results of measurements conducted on various samples and with various cable design parameters, the resistance of a given material (copper or aluminum), expressed as a function of stress, does not depend on the type of force applied. Therefore, the same characteristics may be applied to various cable designs. Practical implications: The method presented in this paper enables more detailed investigation of the influence of particular design parameters on the total resistance of a cable. It also provides the ability to determine optimal settings of design parameters. Originality/value: The approach is distinct from similar studies because it takes into account the deformed geometry of the conductor and the uneven distribution of the resistivity within a filament. In the literature, it is sometimes stated that the distribution of resistivity in a compacted cable is uneven, but its measurement is deemed impossible. This paper provides a method for determining such a distribution.